Fully overlapped rolled hollow section welded joints in trusses - Philiastides, Antony (1988)
The designer of lattice trusses has been traditionally encouraged to avoid extra joint bending moments by ensuring 'noding' of member centre lines. This can however cause problems in the design of RHS trusses with small (economical) branch members by causing large gaps at joints with undesirable flexibility for slender chord walls. 100% overlap joints overcome this problem while still maintaining economic single cut branch ends.